The Effective Analysis for East Karbala Diesel Power Station Photovoltaic System using Homer Pro Software - Haneen Flaih; Mohanad Aljanabi; Bashar Hamza (Journal of Engineering and Sustainable Development)
In Iraq, where electric generation is limited, a pilot work was conducted at East Karbala Diesel Power Station, in Karbala. This aimed to assess the implementation of PV solar systems on stations under both grid-connected and off-grid conditions. We will evaluate various factors, including net present cost, energy cost, operating and initial costs, and annual net energy consumption from the grid. The work analyzed various situations and considered the presence of backup generators (G1-250kVA) at the station. The first step is to conduct a walkthrough energy audit at EKDPS to determine the plant's load profile. By using HOMER Pro, further analysis is illustrated. Results indicated that integrating an on-grid PV system could reduce the cost of energy by 58%, making it the optimal situation when grid power is available. In this case, the Net Present Cost, operating cost per year, was $51,991. Conversely, in the absence of grid power, the best scenario involved a PV system with a 100-kWh lithium battery loading. Despite being the most effective resolution in this situation, the energy cost was 310% greater than the one-case energy rate in Iraq (0.1 $/kWh). Notably, both optimal scenarios did not require generators, highlighting a significant potential benefit for the Nero Zero system.